Adjunct Therapy for CD4+ T-Cell Recovery, Inflammation and Immune Activation in People Living With HIV: A Systematic Review and Meta-Analysis - Zhang, Yang; Jiang, Taiyi; Li, Aixin; Li, Zhen; Hou, Jianhua; Gao, Meixia; Huang, Xiaojie; Su, Bin; Wu, Hao; Zhang, Tong; Jiang, Wei (Frontiers in Immunology, 2021)
Background: HIV infection results in immune homeostasis perturbations, which is characterized by CD4+ T-cell depletion, immune activation, and inflammation. Effective antiretroviral therapy (ART) does not fully restore immunologic and clinical health in people living with HIV (PLWH). Various drugs have been used to improve their immune status and CD4+ T-cell counts, but no measures have been tested effective. Here we conduct a systematic review and meta-analysis of existing clinical studies on improving CD4+ T-cell count while decreasing inflammation and immune activation. Methods: We retrieved possible relevant publications from a total of five electronic databases and selected eligible studies, which dealt with outcomes of medical therapy for CD4+ T-cell count recovery, inflammation, and immune activation with or without ART. We paid particular attention to immunologic non-responders with a favorable treatment regimen. Results: Thirty-three articles were included in the systematic review and meta-analysis. However, there were no safe and effective medications specific for improving CD4+ T-cell reconstitution. The immunological benefits or adverse events mainly depend on the safety, dosage, and duration of the candidate medication use, as well as whether it is combined with ART. Conclusion: Under the “safe, combined, adequate and long (SCAL)” principles, alternative approaches are needed to accelerate the recovery of CD4+ T-cells, and to prevent adverse long-term outcomes in PLWH with standard ART treatment in HIV.